Peran Implementasi Manajemen Rantai Pasokan dalam Perekonomian Era Global (Studi pada Perusahaan Manufaktur di Indonesia) - Anatan, Lina (Zenit, 2012)
Supply chain management is one of  the economic decisions that uses a strategic tool to achieve competitiveness and sustainability in the global economy era. The focus of this study investigate the moderating role of supply chain uncertainty (supplier uncertainty, process uncertainty, demand uncertainty) on the relationship of supply chain management practices and supply chain management performance. Data are collected through mailed questionnaire. The total questionnaires are 500 sent to CEOs firms in Indonesia. Seventy three of useable questionnaires returned yielding the response rate of 14,60%. Through the simple regression the analysis and moderated regression analysis, three hypotheses are supported and one hypothesis is not supported. It means that supply chain management practices have significant effects on supply chain performance, and supply chain uncertainty has a role as moderating variable between the relationship of supply chain management practices and supply chain performance.      Keywords: Supply Chain Management practices, supply chain uncertainty, supply chain performance.